School Management Strategies to a Professional Learning Community for Students’ Quality Development in Schools Under the Education Division 2 - Singkamma, Kraithong (Journal of Dhamma for Life, 2023)
The research objectives are as follows: 1) To investigate the state of school administration in its transition toward becoming a professional learning community, aimed at enhancing the quality of students in schools under the jurisdiction of the Education Department, Region 2. 2) To assess the strengths, weaknesses, opportunities, and threats associated with school administration’s progress toward becoming a professional learning community, with the goal of improving student quality in schools under the Education Department, Region 2. 3) To formulate school administration strategies to advance the transformation into a professional learning community, contributing to the enhancement of student quality in schools under the purview of the Education Department, Region 2. 4) To scrutinize and validate the effectiveness of school management strategies in the pursuit of professional learning community status for the purpose of enhancing student quality in schools under the Education Department, Region 2. Research Results:The research findings are summarized as follows: The conditions of school administration’s transition into professional learning communities, designed to improve student quality in schools under the Office of Education Region 2, encompass five key methods: (1) the establishment of continuous professional learning, (2) the distribution of professional leadership, (3) the promotion of collaboration and trust among staff, (4) the pursuit of support for professional learning, and (5) administrative practices that foster professional learning. The existing state of management to bolster the professional learning community of teachers in schools within Educational Service Area 2, on the whole, achieved a high average level. The aspect of distributing professional leadership scored the highest mean, while the aspect of seeking support for professional learning attained the lowest mean. Strategies for school administration to evolve into a professional learning community, aimed at enhancing student quality in schools under the Ministry of Education, Region 2, consist of five strategic components: (1) the development of a professional learning network, (2) the cultivation of personnel to become part of the professional learning community, (3) the establishment of a culture conducive to professional learning, (4) continuous management of professional knowledge, and (5) the distribution of professional leadership. These strategies have been thoroughly evaluated and certified across four aspects: correctness, suitability, feasibility, and usefulness.